African Handbook of Climate Change Adaptation 2020
DOI: 10.1007/978-3-030-42091-8_155-1
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change, Rural Livelihoods and Ecosystem Nexus: Forest Communities in Agro-ecological zones of Nigeria

Abstract: A top-bottom approach where local problems are treated in isolation has proven ineffective in achieving sustainable development. The need for inclusive approaches to managing the demand for arable lands, forest resources, and the problems of resource exploitation and climate change calls for local understanding of these elements’ interrelationship. Understanding the interrelationships among climate change, agriculture, and the ecosystems in different agroecological zones in Nigeria was the purpose of this chap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This is a proactive decision and leads to upward well-being mobility. The result also agrees with Fadairo et al (2020) who had established the negative implications of environmental changes due largely to human activities on the environment-dependent livelihood and people's well-being.…”
Section: Discussionsupporting
confidence: 90%
“…This is a proactive decision and leads to upward well-being mobility. The result also agrees with Fadairo et al (2020) who had established the negative implications of environmental changes due largely to human activities on the environment-dependent livelihood and people's well-being.…”
Section: Discussionsupporting
confidence: 90%
“…Major constraints reported were insufficient loan ( =2.89), weed infestation ( =2.37), storage losses ( = 2.19), unavailability of land ( =2.13) and low extension activities ( =2.11). The finding that insufficient loan was a constraint to farming in the study area is not far-fetched as most recent studies have revealed the unwillingness of most credit institutions to give loans to farmers due to the general perception that farmers do not repay loans (Appau et al, 2019;Ume et al, 2018) and the high risk associated with crop farming due to the problem of climate change (Fadairo et al, 2020). In addition, the finding is corroborated by Fadairo & keita (2020) who explained poor accessibility to loans for extensive rice production in the Kindia region of Guinea.…”
Section: Knowledge Of Improved Rice Varieties Characteristicsmentioning
confidence: 84%
“…Climate change poses a major threat to poverty reduction and sustainable development worldwide, especially in developed countries (Nigeria inclusive). Nigeria has a vast population that is directly dependent on climate-sensitive economic and development sectors (agriculture and fisheries) as well as natural resources (such as water, biodiversity, and grassland) for sustenance and subsistence (Fadairo et al, 2020). Furthermore, the rural majority's adaptation ability to climate change impacts is very limited.…”
Section: Introductionmentioning
confidence: 99%